Why Is Kant Noncommittal About Grace? - Gressis, Robert (Con-Textos Kantianos. International Journal of Philosophy, 2017)
In Religion within the Bounds of Bare Reason, Kant claims that we may need to invoke divine aid in order to explain how a person can change from evil to good. Kant’s language is a bit curious; why does he not more clearly assert, either that we must posit divine grace, or that we may not? The explanation is this: if we affirm that God grants aid, then this could convince people to passively await it or to think, upon becoming good, that they are part of a special elect. On the other hand, if we affirm that God does not help, then some may despair of ever becoming good while those who successfully change could become arrogant. Thus, Kant is noncommittal about grace because it allows the morally timorous to have hope that they can change, and the morally successful to avoid hubris.